A Carrier Synchronization Algorithm for SDR-based Communication with LEO Satellites - Kozlowski, Sebastian (Společnost pro radioelektronické inženýrství, 2018)
In this work a carrier synchronization algorithm for communication with low Earth orbit (LEO) satellites was proposed. The algorithm has a form of a software routine and is intended to be run on a typical personal computer (PC) providing computational resources for a software defined radio (SDR) receiver. Due to limited computational power of PCs in comparison with other devices, such as FPGAs, the work was focused on providing carrier synchronization with minimal processing. The algorithm includes a nonlinear operation for recovering carrier wave from the received signal, a software 2nd order type 2 phase locked loop for tracking the recovered carrier, and a correction block for removing frequency shift from the received signal. Computer simulations were performed to investigate algorithm’s behavior. Additionally, execution time was measured to determine maximal symbol rate of a signal to be processed.
Keywords: Software defined radio; satellite communication; frequency synchronization; phase locked loop